Obstetric medicine management of medical disorders in pregnancy - Cohen, Wayne R.; August, Phyllis (Peoples Medical Publishing House-USA, 2013)
This book has a distinguished legacy, having begun as the first major American textbook specifically to address complications of pregnancy. Its first edition (Medical, Surgical and Gynecologic Complications of Pregnancy, 1960) was a bellwether that focused attention on what were then nascent interfaces emerging among medicine, surgery, and obstetrics. The 6th edition concentrates on practical issues of clinical management and addresses both common and uncommon medical and surgical problems encountered during pregnancy